Diagnosing Turbulent Magnetic Field in Supernova Remnants - Shimoda, Jiro (Frontiers in Astronomy and Space Sciences, 2022)
We review recent investigations of the statistical nature of turbulent magnetic fields in supernova remnants. After a brief presentation of the role of the magnetic field in the cosmic-ray acceleration and synchrotron emissions from the accelerated electrons, we introduce previous investigations about the turbulent magnetic field in the supernova remnants. Then we describe the new method to analyze the statistical nature of the fields and introduce observational results reported on. Finally, we also discuss about the origin of the turbulent magnetic field and future prospects of observational studies of cosmic-ray acceleration in the supernova remnants.